The use of digital advancement technology in protecting the Longmen Grottoes art - Li, Xiaoshu; Mohd Yusof, Mohd Johari; Ser, Wue Hiong; Perumal, Velu (IOP Publishing, 2021)
Longmen Grottoes, one of the four major grottoes in China, has been listed on the "World Heritage List" and its excavated time was as long as four hundred years ago, which had gone through six different dynasties. Due to the different excavated times, this Buddha statue in each hole or niche has its unique features in clothing, face, body shape and other aspects. Due to climatic changes of wind, rain, frost, and snow, many of these Buddha statues have lost their original appearance. Hence, this study aims to use modern digital restoration technology to restore these grottoes in order enabling many people to appreciate these type of arts through the internet. This method will not only reduce the secondary destruction, but also may allow people to understand and appreciate better the grotto art through the internet. Furthermore, through this restoration, the complete history from a broken Buddha statue can be learned, and even more the culture of ancient China can be explored. The digital restoration of these grotto Buddha statues mainly adopts the modern technological means and detailed research materials of digital virtual restoration, the solemn dharma images that the real thing cannot be traced back are reproduced by virtual technology. The digital simulation is carried out by analyzing the apparel, face, and figure of the Buddha statues in the representative niches of different dynasties. The digital technology for restoring the Buddha statues not only avoids destruction of the Buddhas but also can be seen as efforts in restoring and protecting the grotto art.